The Bundle Theory Dialectic of Attributing the Legal Personality to (AI) A Study of European Artificial Intelligence Law and German Civil law - Jaaz, Muna; Eedan, Qabas; Bashat, Jaleel (Journal of Legal Sciences, 2025)
The Bundle Theory, or Electronic Personhood Theory, in the context of artificial intelligence (AI), is a theory adopted by the European legislature under the Artificial Intelligence Act 2024. It represents a legal and philosophical approach aimed at treating intelligent entities (such as robots and advanced AI systems) as independent legal persons, bearing certain responsibilities or possessing certain rights. The theory suggests that legal personality is not a fixed entity, but rather a bundle of legal attributes (such as financial liability, the right to sue, and liability) that can be granted to entities as needed. This theory has been used to grant legal status to companies and legal entities. Consequently, a future-oriented perspective has emerged, recognizing the legal personality of robots equipped with artificial intelligence, in order to hold them liable for damages that may be caused by their application to advanced AI systems. In our research, we adopted a descriptive approach by reviewing and analyzing conflicting jurisprudential opinions regarding the attribution of legal personality. We also defined the concept of the bundle theory and demonstrated its acceptability, with the aim of assessing the final position of the legal personality of artificial intelligence. Among the results of this study, as an approach to the problem of attributing legal personality, is the possibility of attributing legal personality to artificial intelligence under the bundle theory, considering it an electronic third party, subject to two restrictions: the first is its nature, which prevents it from acquiring certain special family rights; and the second is the restriction of specialization, which limits legal activities to the purpose for which it was created.